Interfacial properties and strengthening mechanisms of few-layered MXene reinforced Mg-based composites - Xiaohao Sun; Xiao Wang; Tongxin Di; Debao Liu (Journal of Materials Research and Technology, 2023)
In the present study, MXene-reinforced Mg matrix composites were manufactured via the electrostatic self-assembly protocol and spark plasma sintering (SPS) process to develop lightweight materials with high mechanical performance. Uniform dispersion of MXene sheets was achieved in MXene/AZ91 composites. A unique interfacial structure was confirmed in these composites, which exhibited an ultrafine MgO interlayer (grain size of ∼10 nm) coherently incorporated or intercalated into MXene layers. The unique interfacial structure contributed to robust interfacial bonding between MXene sheets and Mg matrix, resulting in a substantial mechanical performance enhancement. The yield strength of 325.3 ± 7.9 MPa and elongation of 8.8 ± 0.2% were achieved in 0.3vol% MXene/AZ91 composites, showing a significantly high strengthening efficiency of 159.1 without sacrificing ductility. Quantitatively investigation of strengthening behavior manifested that the load-transfer effect was the primary strengthening mechanism in MXene/AZ91 composites, and the simulated strength was well-matched with experimental results due to the special interfacial structure and excellent dispersion properties. This study could offer significant guidance for developing novel lightweight materials with high mechanical performance for structural applications.